THE RELATIONSHIP BETWEEN THE INDIVIDUAL VALUES OF MOTHERS OF CHILDREN AGED 60 TO 72 MONTHS AND THE PROSOCIAL BEHAVIOR OF THEIR CHILDREN - Türen, Şeyma; Derman, Meral Taner (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2025)
This study examined the relationship between the individual values of mothers of children aged 60 to 72 months and the children’s prosocial behavior. The research was implemented using the relational screening model, a quantitative research method. The study group, which was determined by a simple non-selective sampling method, included 300 children aged 60 to 72 months attending preschool in the Istanbul province of Türkiye in the 2020–2021 academic year, and their mothers. The data collection tools used were the Individual Values Inventory, the Preschool Positive Social Behavior Scale, and a demographic information form. Scores for the mothers in the study group were highest for the values of sharing and respect, and lowest for trust and forgiveness; their children received above-average scores in their prosocial behavior. In addition, there was no statistically significant relationship between the individual values of the mothers and the prosocial behaviors of their children. These findings are discussed and suggestions are made for new research, along with practical ideas for teachers and families.